ACCIDENTS INVOLVING VENOMOUS ANIMALS AND ASSOCIATED FACTORS IN CHILDREN AND ADOLESCENTS - Eleandro Costa, Farley; Rennan Soares Barbosa, Richard; Loreddany Santos Queiroz e Silva, Priscilla; Ferreira Silva, Gleiciane; Borges Evangelista, Christiane; Gabrielle Rodrigues Peixoto, Sarah; Cristina da Silva Andrade, Débora; Rodrigues Santos Guimarães, Junivever; Falcão de Ornelas, Haline; Raielle Aguiar Silveira, Larissa; de Brito Oliva Dias, Cassia; Sabrina Cardoso, Cássia; et al. (Health and Society, 2026)
The objective was to describe the factors associated with accidents involving venomous animals among children and adolescents. An integrative literature review was conducted, analyzing articles retrieved from secondary databases such as the Virtual Health Library, Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online, and the Online System for Searching and Analyzing Medical Literature, using the descriptors “venomous animals,” “child,” and “adolescent,” and Boolean operators. This study evaluated the factors associated with accidents involving venomous animals among children and adolescents. It was observed that 54.5% of the recorded accidents occurred predominantly in the 10-19 year age group, with a higher number of victims being male, a pattern consistent across all “types of causative animals” observed. The results highlight the specific vulnerability of this age group, particularly in rural areas and areas with greater contact with natural environments, where the incidence of snakebites, scorpion stings, and arachnid bites is higher. The identified risk factors, such as lack of adequate supervision, absence or incorrect use of Personal Protective Equipment (PPE) during leisure or work activities/helping with household chores, and lack of knowledge about preventive measures and immediate post-accident management, highlight the need for multifaceted interventions.